2021
DOI: 10.20892/j.issn.2095-3941.2020.0598
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery vs. radiosurgery for the treatment of multiple metastases in the brain: a retrospective cohort study

Abstract: Objective: Multiple brain metastases are a severe condition for cancer patients. To date, no general consensus exists regarding the optimal treatment procedure for multiple brain metastases. Radiotherapy is the most commonly used treatment option. The role of surgical resection for multiple brain metastases is unclear. The aim of this study was to compare the outcomes of patients with multiple brain metastases treated with either surgery or stereotactic radiosurgery (SRS). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, brain as a special site of progression, the choice of local therapy or systemic therapy as the primary treatment has not been determined [21][22][23][24][25][26]. Whole brain radiation therapy (WBRT) is now the standard treatment in many guidelines [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, brain as a special site of progression, the choice of local therapy or systemic therapy as the primary treatment has not been determined [21][22][23][24][25][26]. Whole brain radiation therapy (WBRT) is now the standard treatment in many guidelines [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Even patients presenting with multiple BM have viable treatment options. Surgery and radiosurgery both have comparable tumor control and survival outcomes for patients with 2–4 BM ( 11 ). Separately, a large-scale prospective study included patients with 1–10 newly diagnosed BM and found that stereotactic radiosurgery alone conferred similar survival benefit [HR 0.97, 95% CI 0.81–1.18 (less than non-inferiority margin), p = 0.78; p non-inferiority < 0.0001] and adverse event profiles for patients with a few BM or 5–10 BM ( 12 ).…”
Section: Challenges Of Living With Brain Metastasesmentioning
confidence: 99%
“…The most recent guidelines for the management of patients with BMs provided by the European Association of Neuro-Oncology and the European Association of Medical Oncology (EANO-ESMO) from 2021 [ 2 ] remind that, for optimal therapeutic strategy planning, age, performance score, histotype, and cranial and extracranial disease status should be examined [ 3 ]. Surgery should be considered when there is doubt about the neoplastic nature, when the primary is unknown or the primary rarely generates BMs, when the change in molecular profile can affect the decision making [ 1 ], or when there are acute symptoms of increased intracranial pressure [ 4 , 5 , 6 ]. Stereotactic radiation therapy (SRT) is recommended for patients with a limited number (1 to 9) and size of BMs (typically a cumulative volume lower than 15 cc) [ 2 ] and typically with a Karnofsky performance status (KPS) ≥ 70 and stable extracranial disease [ 7 , 8 ]; SRT is also recommended after surgery for improving local control [ 9 ].…”
Section: Introductionmentioning
confidence: 99%